FREE TIME AND USE OF ALCOHOL AND OTHER DRUGS: A STUDY BETWEEN BRAZILIAN AND PORTUGUESE UNDERGRADUATE STUDENTS - Romera, Liana Abrao; Martins, Raul Aragao [UNESP]; Freitas, Heloisa Heringer; Tinoco, Derick dos Santos; Rondina, Regina Cassia [UNESP] (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2018)
Free time is an integral part of all life stages and is generally associated with leisure, which among youth often comes with the use of alcohol and drugs. The way undergraduate students from Portugal and Brazil use their free time and their patterns of legal and illegal drug consumption are the objectives of this work. The sample included 238 undergraduate students - 60.5% of whom were Portuguese, with an average age of 19.9. Results show that sports practice (31.0%); going out with friends (18.8%): and dating (13.4%) were the three most common activities. Alcoholic beverages and tobacco are the drugs most often mentioned by 50% of the sample. and marijuana use was reported by 15.9%. Heavy alcohol drinking patterns are more common among Brazilian undergraduate students than among Portuguese ones. In conclusion, we stress that these students practice sports but that it do not inhibit alcohol consumption.
Keywords: Alcohol drinking in college; Drug use; Leisure activities; Sports